The Balanced Scorecard in the Public Sector - Nieplowicz, Maria (Zrównoważona karta wyników w sektorze publicznym, 2010)
The main goal of this paper is to introduce the possibilities of using the Balanced Scorecard as a tool which describes the strategy and helps to monitor its realization. In order to adjust the traditional concept of the Balanced Scorecard to the public sector needs, its perspectives have been corrected as to their order as well as their meaning. The article presents examples of using the Balanced Scorecard in a city and in the Internal Audit Department. At the beginning the article presents the general concept of the Balanced Scorecard. Then, there is discussed the Balanced Scorecard for Charlotte and West Des Moines, and the concept of the Balanced Scorecard for Polish city. Next, there is presented the Balanced Scorecard for the Internal Audit Department of the University of North Carolina at Charlotte.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 145, s. 93-102
Keywords: the Balanced Scorecard; public sector; city; internal audit